An Analysis of the Implementation of Diversion in Efforts to Settle Medical Disputes in Indonesia - Arista Candra Irawati; Sarsintorini Putra; Retno Mawarini Sukmariningsih; Adhi Putra Satria (Indian Journal of Forensic Medicine & Toxicology, 2021)
Based on the legal construction contained in Article 29 of Law Number 36 the Year 2009 concerning Health,it has ordered that health workers suspected of neglecting in carrying out their profession. There is a needfor a settlement preceded by the mediation stage or what is known as the settlement of disputes out of thecourt. The facts in the field show that the handling of medical disputes, especially for doctors who commitnegligence, has not been fully implemented according to the provisions of Article 29 of the Health Law,meaning that the handling is not carried out through the first mediation stage, as in the case experienced bydr. Ayu et al. They had to be brought to court accused of committing medical malpractice because they failedto save the patient during a cito-cesarean operation. Dr. Ayu et al. at that time did not fulfill their rights to getmediation. This is because there has been no further regulation governing the procedures, procedures, andrules for implementing mediation, especially health services. Due to this fact, it becomes an obstacle to theconsistency of mediation efforts as a necessity in solving medical disputes. Law No. 29 of 2004 concerningMedical Practice and Regulation of the Medical Council Number 32 of 2015 concerning procedures forhandling suspected disciplinary violations of Doctors and Dentists do not regulate mediation efforts, so theimplementation of mediation efforts in health services is not optimal.